2012
DOI: 10.3109/09553002.2012.666001
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation induces senescence in human adult mesenchymal stem cells from bone marrow and periodontal ligaments

Abstract: Mesenchymal stem cells isolated from bone marrow and periodontal ligament respond to ionizing radiation by induction of stress-induced premature senescence without apparent differences in their radiation response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 40 publications
4
62
0
Order By: Relevance
“…5), transiently upregulated CDKN1A, CDKN2A, and TP53 (Supplemental Fig. 6) and other investigators demonstrated activation of the corresponding signaling cascades on a protein level (Cmielova et al 2012). DNAm profiles were compared before and 7 d after treatment with 15 Gy (n = 4).…”
Section: Gamma-irradiation Does Not Affect Dnammentioning
confidence: 95%
“…5), transiently upregulated CDKN1A, CDKN2A, and TP53 (Supplemental Fig. 6) and other investigators demonstrated activation of the corresponding signaling cascades on a protein level (Cmielova et al 2012). DNAm profiles were compared before and 7 d after treatment with 15 Gy (n = 4).…”
Section: Gamma-irradiation Does Not Affect Dnammentioning
confidence: 95%
“…Stem cell response to harmful stimuli is a prerequisite for the tissue repair and is under active examination (Cmielova et al 2012). In order to fulfill the task of tissue repair, stem cells must remain uninjured under unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis seems to be a general outcome in embryonic stem cells subjected to various stress factors (Sokolov and Neumann 2013). On the other hand, a common stress response of various adult stem cells to different insults is stress-induced premature senescence (SIPS) (Toussaint et al 2000;Brandl et al 2011a, b;Cmielova et al 2012;Ko et al 2012), i.e., appearance of biomarkers of replicative senescence (RS). However, we did not find any indications that HS is also a SIPS trigger.…”
Section: Introductionmentioning
confidence: 99%
“…O'Reilly et al (31) also demonstrated abnormalities in irradiated cultures a number of generations after initial exposure, including convolution of the nuclear envelope, increased incidence of microvilli and lysosomal accumulations, which are characteristic of apoptosis rather than necrosis. However, early senescence as an alternative cause of radiation-induced changes has been discussed for mesenchymal stem cells (MSCs) and fibroblasts (33,34).…”
Section: Discussionmentioning
confidence: 99%